An automated composite table algorithm considering zero liquid discharge possibility in water regeneration–recycle network - Parand, Reza; Yao, Hong Mei; Foo, D.; Tadé, Moses (2016)
In this study, a novel Automated Composite Table Algorithm (ACTA) is developed for targeting the water regeneration–recycle network of single contaminant problem. The ACTA is based on Pinch Analysis, but is automated by taking into consideration the possibility of zero liquid discharge (ZLD) for the water network. In the existing literature, the targeting procedure for ZLD network is based on the graphical tool of Limiting Composite Curve (LCC). However, identification of key parameters (i.e. freshwater, wastewater, regenerated water flowrates, along with pre-regeneration concentrations) is very tedious for highly integrated water network system. The magnification around the turning point of LCC is required to identify the correct pinch points and targeting procedure is done iteratively until the reliable network targets can be determined. These limitations are now overcome by the ACTA, which is an improved version of Composite Table Algorithm that is capable of identifying key parameters algebraically for a given post-regeneration concentration. The newly developed ACTA is capable of handling a wide range of problems including ZLD and non-ZLD network, for both fixed load and fixed flowrate problems.